Usefulness of lithium carbonate, inorganic iodine and plasmapheresis in a patient with severe hyperthyroidism and agranulocytosis due to thiamazole in times of COVID-19 - García-Ruiz, Víctor Raúl (2020)
A 43-year-old woman with a recent diagnosis of Graves-Basedow disease was admitted to the emergency room due to soft tissue infection, thiamazole agranulocytosis, and severe hyperthyroidism. The patient required definitive treatment for hyperthyroidism, but given the context of the SARS-COV-2 pandemic, radioactive iodine was not available, so she prepared for total thyroidectomy. A rapid and effective preoperative preparation was required, so it was decided to compensate her hyperthyroidism with lugol, lithium carbonate, dexamethasone and finally plasmapheresis before surgery. Thyroid hormone levels normalized in a short time, and the thyroidectomy was performed. The case is presented because of the anecdotal and because knowledge of management in scenarios, such as this pandemic, where thereis no access to 131I.